Generation Y entrepreneurial competitiveness: An empirical analysis of determining factors - Khalid, Bilal; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (My University, 2025)
Objective: The research aimed to identify the determining factors that influence Generation Y entrepreneurial competitiveness. The study was motivated by this Generation’s significant impact on the global economy, as they comprise a quarter of the global population, and the fact that they grew up in a period of technological advancement. Research Design & Methods: We used a quantitative survey research design to empirically collect primary data from Gen Y entrepreneurs, using a sample size of 384 respondents. The model had six independent vari-ables, i.e., personal traits, entrepreneurial self-efficacy, networking skills, digital capabilities, fear of failure, and growth mindset. The mediating variable was entrepreneurial orientation, while the dependent variable was entrepreneurial competitiveness. We evaluated the model using confirmatory factor analysis (CFA), and we tested the hypotheses using structural equation modelling (SEM). Findings: We found that entrepreneurial self-efficacy, digital capabilities, networking skills, and growth mindset significantly enhance Gen Y competitiveness, while personal traits showed no significant effect. Fear of failure had an unexpected positive impact. Entrepreneurial orientation did not mediate these re-lationships. Innovation and adaptability were key drivers, but digital transformation emerged as the strongest predictor of Gen Y entrepreneurial success in competitive markets. Implications & Recommendations: The study recommended Gen Y entrepreneurs and policymakers entrepreneurial training and education to enhance their entrepreneurial capabilities; networking strategies and skills, which are vital in nurturing a diverse workforce; and digital transformation for small businesses as a strategy to achieve entrepreneurial competitiveness. Contribution & Value Added: Our research advances entrepreneurial research by identifying key drivers of Gen Y competitiveness: digital capabilities, self-efficacy, and networking, while challenging conventional as-sumptions about personal traits and fear of failure. It bridges gaps in generational entrepreneurship literature by empirically validating technology’s pivotal role. The findings offer a refined framework for policymakers and educators to cultivate adaptive, digitally fluent entrepreneurs, enhancing competitiveness in evolving markets. This work enriches theoretical discourse and provides actionable strategies for fostering Gen Y entrepreneurial success by integrating psychological and technological perspectives.
Keywords: digital capabilities; entrepreneurial competitiveness; entrepreneurial orientation; entrepreneurial self-efficacy; generation Y